Salmonellosis: complicaciones extra-intestinales - Dominguez Navarrete, Nicanor (1973)
Fourteen patients with unusual type of Salmonellosis (extra.intestinal), are studied, nine of these patients were under two years of age. The date was obtained from 7,500 cultures done on purulent secretions and spinal fluid during a period of seven years (1965-1971) and collected at the Microbiology Service of the Children Hospital of Lima.